Three dimensional data manipulation and representation for accurate and realistic data visualization - Penner, R.B.; Durdle, N.G.; Raso, V.J.; Hill, D.L. (1995 IEEE International Conference on Systems, Man and Cybernetics, 1995)
A realistic method of visualizing random depth maps of the human back is described. A realistic surface was created that can be used in the assessment of subjects with scoliosis. Methods are presented to remove the effects of noise and to create a realistic solid surface that can be viewed and manipulated in three dimensions. Automated techniques of triangulation, resampling, noise reduction and various screen representations are discussed. This work determines the best techniques for representing a back surface, with the criteria being: realism of presentation; and accuracy.